2023
DOI: 10.3390/ma16020665
|View full text |Cite
|
Sign up to set email alerts
|

Friction Reduction by Dimple Type Textured Cylinder Liners—An Experimental Investigation

Abstract: Applying texture to a surface in a tribological interface will influence frictional performance, which has been investigated in several previous studies. However, since varying operating conditions heavily affect the frictional performance and optimum texture dimensions, more work in this field is required. There are few experimental studies concerning the influence of texture on friction especially under sliding lubricated conditions and even fewer at high sliding speeds. In this work, the effect of texture o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…It has been gained more and more attention in recent years (Chen et al , 2021; Wahab et al , 2016; Costa and Hutchings, 2015). Numerous studies have shown that surface texturing techniques can improve the wear resistance, lubricity, corrosion resistance and other properties of materials, which extend their service life (Wang et al , 2023; Söderfjäll and Gachot, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…It has been gained more and more attention in recent years (Chen et al , 2021; Wahab et al , 2016; Costa and Hutchings, 2015). Numerous studies have shown that surface texturing techniques can improve the wear resistance, lubricity, corrosion resistance and other properties of materials, which extend their service life (Wang et al , 2023; Söderfjäll and Gachot, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the nature and chemical composition of the materials of the parts involved in the friction process on some tribological properties of different categories of materials [3,12,14,[24][25][26][27]; -Sizes used to characterize friction processes between textured surfaces, with or without lubricant [3,11,28]; -…”
Section: Introductionmentioning
confidence: 99%
“…The influence of the texturing on the adhesion between surfaces [2,14]; -Surface texturing inspired by nature [5,14,25]; -Numerical simulation of aspects corresponding to friction processes involving textured surfaces [3,4,25,27]; -…”
Section: Introductionmentioning
confidence: 99%